Potential applications and adverse effects of bisphenol a in humans - Bhat, A.H. (Nova Science Publishers, Inc., 2014)
Bisphenol A (BPA), an organic chemical, has been in widespread use since decades for the manufacture of polycarbonates and epoxy resins. Due to the ubiquity of downstream applications, BPA is ranked among the top industrial chemicals with the highest production volumes in the world. With the fall of the key end-use sectors during the economic recession, the end-use market for polycarbonates and epoxy resins declined significantly, thereby resulting in a loss-making scenario for Bisphenol A and phenol producers across the world. However, the market quickly bounced back in sync with the recovery of the global economy. Strong global appetite for BPA-based Polycarbonate Plastics and epoxy resins continues to spur growth in the global market. BPA in turn remains a major driver for the growth of the upstream phenol and acetone markets, with emerging economies. Bisphenol A is one of the extensively tested chemicals in commerce today. BPA has been safely used since many years, and has been the subject of many scientific studies by researchers around the globe. Containers made with these plastics may expose people to small amounts of BPA in food and water. Medical devices and other more common products, such as thermal paper coatings, also may contribute significantly to human exposure. Some animal experiments have found that fetal and infant development may be harmed by small amounts of BPA, but scientists disagree about the value of the animal studies for predicting harmful effects in people. There is scientific disagreement about the possibility of human health effects that may result from BPA exposure has led to conflicting regulatory decisions regarding the safety of food containers, especially those intended for use by infants and children. It is reported that some companies are exploring alternatives to BPA-containing food cans. This chapter will discuss comprehensively various potential applications and harmful effects of BPA on human health. Â© 2015 by Nova Science Publishers, Inc. All rights reserved.